Conjugal Love and Procreation: Dietrich von Hildebrand's Superabundant Integration - Schemenauer, Kevin (Lexington Books, 2011)
Dietrich von Hildebrand contributed to the Catholic tradition's increased recognition of conjugal love in marriage in the early twentieth century, and, as Kevin Schemenauer argues in Conjugal Love and Procreation, von Hildebrand's work remains relevant to contemporary Catholic thought as well. While some argue that this German Catholic philosopher and theologian neglected the role of procreation in marriage, this book shows that von Hildebrand's writings on reverence and superabundant finality contribute to a contemporary understanding of the significance of procreation within marriage. Schemenauer analyzes von Hildebrand's integration of conjugal love and procreation, showing him to be an insightful and parallel voice to the that of John Paul II. His thorough exploration of von Hildebrand's writings reveals not only how conjugal love and openness to new life are essential to marriage, but also how essential the role of procreation is to the conception of conjugal love.